Expansion of Habenaria to include Cooktownia, Diplomeris, Herminium, Pecteilis and Peristylus (Habenariinae; Orchidaceae) - Chase, Mark W.; Jin, Xiaohua; Christenhusz, Maarten J. M.; Schuiteman, André (Phytotaxa, 2026)
To remedy the non-monophyly of Habenaria as demonstrated in several phylogenetic analyses, we propose here to expand the limits of the genus to include the species of Cooktownia, Diplomeris, Herminium, Pecteilis and Peristylus. Previously, Androcorys, Bhutanthera, Frigidorchis and Porolabium were synonymised with Herminium, and Bonatea, Centrostigma, Platycoryne and Roeperocharis with Habenaria. The proposed 16 new names and 69 combinations make Habenaria among the largest genera of Orchidaceae with roughly 1160 species.